Enabling electrochemical compatibility of non-flammable phosphate electrolytes for lithium-ion batteries by tuning their molar ratios of salt to solvent. Issue 48 (12th May 2020) - Liu, Xingwei; Shen, Xiaohui; Zhong, Faping; Feng, Xiangming; Chen, Weihua; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract : A stable phosphate electrolyte with a high molar ratio (1 : 2) but a low molar concentration (1.35 M) is developed. Abstract : We develop a new type of electrolyte with a high molar ratio (MR) of salt to solvent but a low molar concentration by adjusting the molar mass of the solvent. The present 1 : 2 LiFSI–triamyl phosphate electrolyte exhibits a low molar concentration of only 1.35 M along with excellent electrochemical stability against the graphite anode.